Analysis of the Relationship Between HIV/AIDS Clinical Stage and Opportunistic Infections at Hospital X - Chinthia Devientasari; Selly Septi Fandinata (Strada Journal of Pharmacy, 2026)
Opportunistic infections remain a major cause of morbidity and mortality among people living with Human Immunodeficiency Virus (HIV). The progressive decline in immune function increases susceptibility to infections such as tuberculosis, candidiasis, and toxoplasmosis. The World Health Organization (WHO) clinical staging system is widely used to assess HIV disease progression and is often associated with the occurrence of opportunistic infections. This study aimed to analyze the association between HIV clinical stage and opportunistic infections among HIV/AIDS patients at Hospital X. This study employed an observational analytic design with a cross-sectional approach. Data were obtained from medical records of HIV/AIDS patients, with a total sample of 193 patients selected using total sampling. Statistical analyses included univariate and bivariate analyses using the chi-square test. The majority of patients were in clinical stage III (80.3%). The prevalence of opportunistic infections was 14.0%. The results of the chi-square test showed no significant association between clinical stage and opportunistic infections (p = 0.206). Although opportunistic infections were more frequently observed in advanced stages, the relationship was not statistically significant.